The Role of Intangible Assets and Digital Technologies In Value Creation in Digital Business Models - Grzegorz URBANEK (Communications of International Proceedings, 2022)
The aim of a paper is to present the role of intangible assets and digital technologies in value creation in digital business models. The considerations in the article are presented on the background of the extensive integrative literature review. The article uses the method of critical analysis and synthesis of opinions of other authors as well as logical inference together with elements of case study analysis. The digital technologies and assets enhance the value creation potential of traditional intangible assets. The development of digital technologies causes a multiplier effect in business value creation. By combining intangible assets with digital technologies, companies can effectively scale their operations that result in significant value appreciation, due to the elimination of traditional internal and external growth constraints. The study forms a theoretical framework based on a literature review enriched with limited input from practical cases. Subsequent research direction should aim toward quantitative analysis of the contribution of different types of intangible assets and digital technologies, to value creation. The study enhances theory on understanding of the role of intangible assets and related digital technologies in value creation in the digital era and argues that intangible assets form the foundation of effective business models. The findings of the study can help managers in the successful implementation of digital transformations in their companies by indicating the most crucial areas of concern in this process related to intangible assets.
Keywords: Intangible Assets; Digital Technologies; Value Creation; Digital Business Models.